To what extent do policies from across 5 countries in the Middle East and North Africa region integrate climate-related security concerns and risks? - Schapendonk, Frans; Scartozzi, Cesare M.; Kurath, Tina; Meddings, George; Madurga Lopez, Ignacio M.; Savelli, Adam; Pacillo, Grazia; Läderach, Peter R.D. (CGIAR FOCUS Climate Security, 2022)
This factsheet presents the main results of a policy coherence analysis focused on climate security in Middle East and North Africa